Geostrategic Imperatives and Prospects: Re-conceptualizing Nepal's Foreign Policy amidst a Transforming Global Landscape - Gautam, Dilli Raj (Dhaulagiri Journal of Contemporary Issues, 2025)
This paper highlights the geostrategic imperatives that encompass the essential strategic priorities. A nation must address to safeguard its sovereignty, security, and national interests within the context of its geographic positioning and global geopolitical dynamics. Nepal's foreign policy focuses on balancing its strategic location between India and China while managing regional and international alliances to safeguard national interests. Since King Prithvi Narayan Shah's era, Nepal has followed a non-aligned approach, likening itself to a "yam between two boulders." Despite occasional tilts toward either neighbor, Nepal has generally sought diplomatic balance. A major shift occurred after the promulgation of new constitution in 2015. Afterwards, the elected government emphasized trade and transit diversification, particularly strengthening ties with China. This paper explores the historical development of Nepalese foreign policy and examines how it is being redefined in a changing global context. The existing literature is still insufficient to fully reveal Nepal's foreign policy priorities in the current scenario. This article is basically an analytical overview of foreign policy in reference to federal context of Nepal. Contrasting the previous relevant research articles, the author has focused on a qualitative approach based on secondary textual data. Relevant journal articles, books, and authentic websites are reviewed while preparing this article. For Nepal, to establish a unified foreign policy that reflects its long-standing political stability, all political parties must work together and harmonize their approaches for ensuring national interests as defined in the new constitution.